2022
DOI: 10.1101/2022.09.08.22279731
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Dynamics of SARS-CoV-2 seroassay sensitivity: a systematic review and modeling study

Abstract: We performed a systematic review and meta-analysis of SARS-CoV-2 serology studies to estimate time-dependent sensitivity for a large set of serological assays. We find that seroreversion depends strongly on the antigen and the analytic technique of the assay. We estimate the average time-varying sensitivity for different types of assays, as defined by their technical characteristics, which can be used to approximate the sensitivity of out-of-sample assays. We find large variability between types of assays, wit… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 116 publications
0
5
0
Order By: Relevance
“…This waning, especially of N-specific antibodies, may have caused us to underestimate infection-induced SARS-CoV-2 exposure. Variability in commercial anti-N antibody assay performance suggests faster waning of N-specific antibodies may be related to assay characteristics rather than biological waning ( 46 48 ). We used a quantitative antibody assay, which generally perform better than lateral flow assays ( 48 ).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…This waning, especially of N-specific antibodies, may have caused us to underestimate infection-induced SARS-CoV-2 exposure. Variability in commercial anti-N antibody assay performance suggests faster waning of N-specific antibodies may be related to assay characteristics rather than biological waning ( 46 48 ). We used a quantitative antibody assay, which generally perform better than lateral flow assays ( 48 ).…”
Section: Discussionmentioning
confidence: 99%
“…Variability in commercial anti-N antibody assay performance suggests faster waning of N-specific antibodies may be related to assay characteristics rather than biological waning ( 46 48 ). We used a quantitative antibody assay, which generally perform better than lateral flow assays ( 48 ). Assays targeting RBD generally have the slowest decay and loss of sensitivity over time, followed by S, followed by N; our multiplex approach incorporating both RBD and N may have allowed us to maintain sensitivity with a lower N cutoff ( 43 , 48 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Antibody titers may decline over time. For example, a modelling study estimating the average time from seroconversion to seroreversion at 3-4 months (11) and other investigators have also found steep decreases in antibody assay sensitivity over time (12) and a systematic review found large variability in seroreversion rates across assays and studies (13). Therefore, for consistency, if there were multiple different time points when seroprevalence was assessed in a given study, we selected the one that gave the highest seroprevalence estimate and when there was a tie we chose the earliest one (in a sensitivity analysis, we excluded from the calculations studies where the chosen time point was not the latest).…”
Section: Methodsmentioning
confidence: 99%